Congenital Dermal Sinus and Limited Dorsal Myeloschisis: "Spectrum Disorders" of Incomplete Dysjuction Between Cutaneous and Neural Ectoderms. Issue 2 (29th March 2018) - Lee, Ji Yeoun; Park, Sung-Hye; Chong, Sangjoon; Phi, Ji Hoon; Kim, Seung-Ki; Cho, Byung-Kyu; Wang, Kyu-Chang
Abstract: BACKGROUND: The existence of tethering tracts in spinal dysraphism, other than congenital dermal sinus (CDS), has been recognized and has been summated into an integrated concept of limited dorsal myeloschisis (LDM). OBJECTIVE: To elucidate the underlying embryology of LDM in relation to CDS by focusing on the pathological features of special cases of tethering tracts. METHODS: Out of 389 spinal dysraphism patients who were operated on from 2010 to 2016, 5 patients who had tethering tracts composed of both CDS and LDM (or "probable LDM" if only fibrous tissue was found) were identified. Their clinical presentation, radiological images, operative findings, and pathology were thoroughly reviewed. RESULTS: Three nonsaccular-type patients harbored stalks in which the squamous epithelial lined sinus (CDS) was found in the distal portion, and fibroneural (LDM) or fibrous (probable LDM) tissue in the proximal part. Two patients had saccular lesions, and a stalk was found inside the sac, connecting a small pit on the skin to the spinal cord. The tracts were pathologically identical to a CDS. CONCLUSION: This study reports the coexistence of CDS and LDM (or probable LDM) components. These unique cases support the hypothesis that the CDS and LDM are among a spectrum of an anomaly that is caused by failure of complete dysjunction between cutaneous and neural ectoderms. Neurosurgeons should be aware of the possibility of coexisting "CDS" components in cases suggestive of LDM. In such cases, not only untethering but also meticulous removal of the squamous epithelium is critical.